Antarctic yeasts: potential use in a biologic treatment of textile azo dyes - Ruscasso, María Florencia (2022)
We investigated the dye-removal potential of a collection of 61 cold-adapted yeasts from the King George Island, Antarctica, on agar plates supplemented with 100 mg L⁻¹ of several textile dyes; among which isolates 81% decolorized Reactive Black 5 (RB-5), with 56% decolorizing Reactive Orange 16, but only 26% doing so with Reactive Blue 19 and Acid Blue 74. Furthermore, we evaluated the ligninolytic potential using 2,2ʹ-azino-bis(3-ethylbenzothiazoline-6- sulfonic-acid) diammonium salt-, 3,5-dimethoxy-4-hydroxybenzaldehydazine-, or manganese-supplemented plates but detected no activity, possibly due to a dye-removal mechanism involving reductases. The removal kinetics were studied in liquid medium supplemented with 100 mg L⁻¹ of RB-5 in a selection of 9 yeasts. The highest volumetricremoval rates (η) were found for Candida sake 41E (4.14 mg L⁻¹ h⁻¹), Leucosporidium muscorum F20A (3.90 mg L⁻¹ h⁻¹), and Cystofilobasidium infirmominiatum F13E (3.90 mg L⁻¹ h⁻¹). Different UV–Vis spectra were obtained if the dye removal occurred by biodegradation or biosorption/bioaccumulation. L. muscorum F20A was selected to study the dye-removal mechanism of RB-5 and the effect of different chemical and environmental parameters on the process. Optimum dye-removal conditions were obtained with 10 g L⁻¹ of glucose within an initial medium pH range of 5.0 to 6.0. Up to 700 mg ⁻¹ of dye could be removed in 45 h. High-performance liquid chromatography profiles obtained were consistent with a biodegradation of the dye. Phytotoxicity was estimated by calculating the 50%-inhibition concentration ( IC50) with Lactuca sativa L. seeds. These findings propose psychrophilic yeasts as a novel environmentally suitable alternative for the treatment of dye-industry wastewaters.